Hydrothermal Conversion of Rice Husk on Solid Acid Catalysts - Huang, Xigen; Bai, Ailing; Le, Guan; Huang, Yanqiu; Le, Zhiping (Asian Journal of Chemistry, 2015)
Liquefaction of rice husk using hydrothermal treatment with solid catalyst was investigated. Study shows that all solid catalysts tested exhibited high catalytic activities. The solid acid catalysts have higher activity than other catalysts. The catalysts were characterized by FT-IR and NH3-TPD. The result of FT-IR shows that the Cl– of catalyst is in the form of ClO4–; therefore, ClO4–-Fe2O3-La2O3/ZrO2-SiO2 can be made into solid super acid catalysts. The result of NH3-TPD indicates that ClO4–-Fe2O3-La2O3/ZrO2-SiO2 catalyst has two kinds of surface acidity sites. GC-MS analysis shows that the major conversion products were phenol, 3-methyl-1, 2-cyclopentanedione, 6-methoxy-8-nitro-4-trifluoromethylquinoline and 2-methoxy-phenol. The liquefaction characteristics were found to be influenced by the reaction conditions including temperature, holding time, catalyst dosage and water to rich husk (W/R) ratio.